2016
DOI: 10.1016/j.neuroscience.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal fat-rich diet exposure alters responses of embryonic neurons to the chemokine, CCL2, in the hypothalamus

Abstract: Maternal consumption of a high fat diet (HFD) during pregnancy is found to stimulate the genesis of hypothalamic orexigenic peptide neurons in the offspring, while HFD intake in adult animals produces a systemic low-grade inflammation which increases neuroimmune factors that may affect neurogenesis and neuronal migration. Building on this evidence and our recent study showing that the inflammatory chemokine, CCL2, stimulates the migration of hypothalamic neurons and expression of orexigenic neuropeptides, we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…Some chemokines could also be involved in the embryonic development of certain hypothalamic neurons, which are important for energy balance. Recently, it was shown that prenatal HFD feeding can alter gene expression of chemokines such as CXCL12 and CCL2 in the hypothalamus and thus affect the development of hypothalamic orexigenic neurons in the offspring (Poon et al, 2016a(Poon et al, , 2017. Also, CCL5 deficiency was shown to affect hypothalamic insulin signaling in a genetic mouse model (Chou et al, 2016).…”
Section: Il-4mentioning
confidence: 99%
“…Some chemokines could also be involved in the embryonic development of certain hypothalamic neurons, which are important for energy balance. Recently, it was shown that prenatal HFD feeding can alter gene expression of chemokines such as CXCL12 and CCL2 in the hypothalamus and thus affect the development of hypothalamic orexigenic neurons in the offspring (Poon et al, 2016a(Poon et al, , 2017. Also, CCL5 deficiency was shown to affect hypothalamic insulin signaling in a genetic mouse model (Chou et al, 2016).…”
Section: Il-4mentioning
confidence: 99%
“…Preclinical animal models have demonstrated fetal exposure to diet-induced obesity results in neural reprogramming in multiple brain regions and neuroendocrine systems ( 12 15 ). Importantly, these diet-induced neurodevelopmental and behavioral aberrations are associated with altered neuroinflammatory response ( 16 18 ). Inflammation is believed to be crucial to perinatal behavioral programming ( 19 , 20 ), and human studies support a link between increased inflammatory factors and neurodevelopmental disorders ( 21 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kim and colleagues identified increased proliferation in astrocytes, suggesting overall changes in proliferative capacity in different cellular populations of the CNS (62). In addition to the changes in generation and proliferation of cells, Poon and colleagues also show a decreased migratory ability of neurons, specifically hypothalamic neurons, in response to increasing concentrations of the potent chemokine, CCL2 (63). Overall, alterations in neurogenesis and proper cell migration are associated with maternal highfat diet intake.…”
Section: Neurogenesismentioning
confidence: 98%